Fondasi Alkitabiah Dalam Pengembangan Kurikulum PAK Dan Moralitas Bagi Pelajar - Gostin Gostin (Jurnal Teologi Injili dan Pendidikan Agama, 2023)
In this era of modernization, many changes have occurred in human life, so it is very important to teach religious education in schools with the aim of contributing to the morale of students who are increasingly far from God's truth. Therefore, education must rest on the four pillars, viz. know, learn to do, learn to live together and learn to be yourself. What is very important in competency development is the curriculum as a learning tool. In this case, the curriculum is considered to be able to solve various problems of the nation, especially in the field of education, by training students, planning, implementing and evaluating the education system in an effective, efficient and effective manner.